Analysis of Fifth Grade Students' Mathematical Problem-Solving Skills in Whole-Number Operations Based on Polya's Stages - Adhitya, Sandry; Sujana, Atep; Mulyasari, Effy (International Conference on Elementary Education, 2025)
This study aims to analyze the mathematical problem-solving abilities of fifth-gradeelementary school students in whole-number operations, using Polya's stages as a reference. This studyuses a qualitative descriptive method with data collection through problem-solving tests and interviews.The tests were used to assess students' abilities across the four stages of Polya: understanding theproblem, planning the solution, implementing the plan, and checking the results. Meanwhile, interviewswere conducted with several students to explore their reasons for choosing the strategy, their thoughtprocesses, and the difficulties they encountered while solving the problems. The research subjectsconsisted of 34 fifth-grade students at a public elementary school in Cimahi City. The results showedthat the problem understanding stage had the highest percentage of 86.2% (high category), followed bythe planning stage with 71.8% (medium category). The stages of implementing the plan and checkingthe results each reached 48.2% and 46.4% (low category). These results confirm that students canunderstand the information in the questions but still experience difficulties applying strategies andchecking results, so it is necessary to strengthen learning in these two stages to optimize problemsolving skills.